Effects of Financial Literacy and Financial Management Teaching on Financial Behavior (Student Study of Hotel & Tourism Business Study Program) - Siska Septian Andriyani; Lexi Pranata Budidharmanto; Yopy Junianto (Fakultas Bisnis, 2022)
Financial literacy is an important factor in improving people's economic welfare. When a person's financial literacy is high, it is certain that the quality of life and welfare will also increase. This can happen because of the higher one's financial literacy, the better one's financial behavior. Students are the driving force of the nation's economy because students have the largest population, character, and literacy level. However, students are also faced with various very complex financial problems because some students still do not have their own source of income while the level of student needs is high. For this reason, students need to gain more knowledge about financial literacy through financial management learning models in their courses. This was done by the Hotel & Tourism Business study program at Ciputra University, Surabaya batch 2019 and 2020. However, in the process, it is necessary to evaluate the effectiveness of whether teaching changes the financial behavior of students. We used linear regression analysis to process the data in this study. Based on the description above, this study aims to find the effect of financial literacy on financial behavior with financial management teaching as a moderation. The results of this study indicate that there are significant differences in perceptions related to financial behavior between someone who has high and low financial literacy, while the teaching of financial management has a positive effect in moderating the relationship between financial literacy and financial behavior but is not significant.